Glymphatic dysfunction evidenced by DTI-ALPS is related to obstructive sleep apnea intensity in newly diagnosed Parkinson’s disease - Jiri Nepozitek; Stanislav Marecek; Veronika Rottova; Simona Dostalova; Tomas Krajca; Jiri Keller; Karel Sonka; Petr Dusek (npj Parkinson's Disease)
Abstract Glymphatic dysfunction potentially contributes to Parkinson’s disease (PD) via impaired clearance of metabolic waste products. Obstructive sleep apnea (OSA) can disturb sleep, which is necessary for proper glymphatic function, and is frequent in PD. We investigated the glymphatic function in de novo PD and its relation to OSA. Fifty-four PD patients (mean age 58.9 ± 12.2 years) and 32 controls (mean age 59.4 ± 8.3 years) underwent polysomnography and 3 T magnetic resonance imaging of the brain. Diffusion tensor imaging along the perivascular space (DTI-ALPS) was calculated using atlas-based automatic regions of interest selection. In PD, ALPS-index negatively correlated with apnea-hypopnea index (rho = −0.41; p = 0.002), oxygen desaturation index (rho = −0.38; p = 0.006), sleep stage N1 (rho = −0.42; p = 0.002), and arousal index (rho = −0.24; p = 0.018), while in controls, no such correlations were observed. Glymphatic dysfunction is related to OSA severity in de novo PD but not in controls. We suggest that OSA may contribute to neurodegeneration via glymphatic impairment in PD.